The influencing factors and employee performance in banking sector in Ningxia China - Yew, Lim Kim; Mei , Hu; Kowang, Tan Owee; Chen, Yang; Udang, Lester Naces (International Journal of Innovative Research and Scientific Studies, 2025)
There are many studies on employee performance, but few studies on employee performance focus on the banking industry in underdeveloped western China. This study explores the relationship between four influencing factors, namely work environment, training, leadership, and work flexibility, and employee performance in the banking industry in Ningxia, China. This study adopts a quantitative research method and collects data through questionnaires. The results of data analysis show that the work environment and leadership are significantly positively correlated with employee performance in the banking industry in Ningxia, but training and work flexibility are significantly negatively correlated with employee performance in the banking industry in Ningxia. This empirical study proves that in terms of how to improve employee performance and employment protection in the banking industry.